2017
DOI: 10.4186/ej.2017.21.1.155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Atomization Parameters on Size and Morphology of Al-17Si Alloy Powder Produced by Free Fall Atomizer

Abstract: Abstract:The effect of process parameters on the characteristics of Al-17Si alloy powder produced by gas atomization using a free fall nozzle of different apex anglesof different apex angles was investigated. The axial gas velocity of gas jet away from the nozzle exit is measured for different operating pressures. The alloy was melted to a superheat temperature of 100,150 and 200°C and atomized by varying the gas flow rate and melt flow rate. The alloy powder size analysis were carried out by ASTM standard sie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The powder characteristics, such as the particle size distribution and yield ratio, produced by GA are influenced by several parameters, such as the atomizing gas pressure, melt superheat, and the gas-to-metal ratio (G/M) [112]. It is found that the increase in air pressure, melt superheat and G/M decrease the median particle size, and increase the sphericity for the Al-17Si alloy powders [113]. Martin et al [114] showed that increasing atomizing gas pressure substantially improves the yield ratio of particles with sizes smaller than 150 µm.…”
Section: Gamentioning
confidence: 99%
“…The powder characteristics, such as the particle size distribution and yield ratio, produced by GA are influenced by several parameters, such as the atomizing gas pressure, melt superheat, and the gas-to-metal ratio (G/M) [112]. It is found that the increase in air pressure, melt superheat and G/M decrease the median particle size, and increase the sphericity for the Al-17Si alloy powders [113]. Martin et al [114] showed that increasing atomizing gas pressure substantially improves the yield ratio of particles with sizes smaller than 150 µm.…”
Section: Gamentioning
confidence: 99%
“…We could also observe the effect of black spots, spherical imperfections since we found coaks or craccks on several parts of the powder surface. Coaks or cracks on the surface could have occured as a result of melt disintegration mechanisms during the gas atomization process [14] that had not formed the perfect spherical droplets completely; however, it collided first with other particles that had been solidified and hit the surface of the atomizer device and then it was cooled down after meeting the water at the bottom of the atomizer. This thing also made a number of coarse powders attached to small powders on the surface.…”
Section: Fig 5 Graph Of the Effect Of Melt Flow Rate On Powder Morpho...mentioning
confidence: 99%
“…Among them, carbon coating refers to coating a layer of carbon shell on the surface of nano-aluminum particles to form a core-shell structure of carbon-coated aluminum. The most direct role of the carbon shell on the surface of nano-aluminum powder is to isolate the contact between core aluminum and outside air to maintain Activity of nano-aluminum powder [9][10]. In addition, the carbon layer can burn quickly under high heat conditions, and the core aluminum is exposed to the high heat environment for combustion.…”
Section: Introductionmentioning
confidence: 99%